2007
DOI: 10.1124/jpet.106.117507
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity of Hallucinogenic Phenethylamine and Phenylisopropylamine Derivatives at Human 5-Hydroxytryptamine (5-HT)2A and 5-HT2C Receptors

Abstract: 2,5-Dimethoxy-4-substituted phenylisopropylamines and phenethylamines are 5-hydroxytryptamine (serotonin) (5-HT) 2A/2C agonists. The former are partial to full agonists, whereas the latter are partial to weak agonists. However, most data come from studies analyzing phospholipase C (PLC)-mediated responses, although additional effectors [e.g., phospholipase A 2 (PLA 2 )] are associated with these receptors. We compared two homologous series of phenylisopropylamines and phenethylamines measuring both PLA 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 38 publications
3
118
1
1
Order By: Relevance
“…Some of these differences are noteworthy; for example, in psilocin, the potency for activating AA release was nearly 30-fold greater than for stimulating PI turnover. Moya et al (2007) compared two homologous series of substituted psychedelic phenethylamines and phenylisopropylamines for signaling at the 5-HT 2A receptor through PLC and PLA 2 responses. They employed Chinese hamster ovary (CHO)-FA4 cells stably expressing the human 5-HT 2A receptor that had similar maximal responses for inositol phosphate (IP) accumulation and AA release in response to serotonin.…”
Section: Functional Selectivity At the Serotonin 5-hydroxytryptamimentioning
confidence: 99%
“…Some of these differences are noteworthy; for example, in psilocin, the potency for activating AA release was nearly 30-fold greater than for stimulating PI turnover. Moya et al (2007) compared two homologous series of substituted psychedelic phenethylamines and phenylisopropylamines for signaling at the 5-HT 2A receptor through PLC and PLA 2 responses. They employed Chinese hamster ovary (CHO)-FA4 cells stably expressing the human 5-HT 2A receptor that had similar maximal responses for inositol phosphate (IP) accumulation and AA release in response to serotonin.…”
Section: Functional Selectivity At the Serotonin 5-hydroxytryptamimentioning
confidence: 99%
“…Consistent within other hallucinogens, no clear correlation was found between binding affinity to the 5-HT 2A receptor and its functional activation potency (Nichols et al, 2015). Importantly, 5-HT 2A receptor activation is measured using various in vitro assays that reflect the activation of 17 different second messenger systems (Moya et al, 2007;Nichols, 2004), and these measures may apparently not reflect the mechanisms that mediate the subjective effects of these hallucinogens.…”
Section: Discussionmentioning
confidence: 79%
“…-Methyl-5-HT and fluoro-α-methyltryptamines were shown to be more potent than their non--methylated analogs in inducing hallucinogen-typical head-twitch responses in mice (Nakagawasai et al, 2004;Tadano et al, 1995). Similarly, the α-methylation of phenethylamines increased 5-HT 2A receptor stimulation efficacy and head-twitch responses (Moya et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of monoamine contents in brain, especially 5-HT, is known to cause several abnormal behaviors in animals, such as HTR and head-weaving (Kim et al, 1998). It is also reported that HTR is induced by 5-HT 2A receptor stimulation in the prefrontal cortex (Willins and Meltzer, 1997;González-Maeso et al, 2003;Nakagawasai et al, 2004;Moya et al, 2007). It was documented for the first time that 5-HT 7 receptor stimulation is also able to produce HTR (Figure 2).…”
Section: Discussionmentioning
confidence: 95%